Photographs and Personal Memory in Ana Menendez’s Loving Che - Rarastesa, Zita; Susilorini, Susilorini; Kusumo Habsari, Sri; Mugijatna, Mugijatna; Kusdianto, Yuyun (Journal of Social Science, 2024)
This paper points out the issues of personal history versus mainstream/official history, the changing meaning of photographs, the concept of truth/fact, and personal identity in Ana Menendez’s novel Loving Che. The unnamed main character in this novel tries to construct her identity based on her mother's diary and letters as well as the photographs her mother sent to her. She and her mother, Teresa de La Landre, were separated due to a political dispute in Cuba. Teresa managed to get her father and baby out of Cuba and fled to Miami. When Teresa's father arrived in Miami, only then did he realize that Teresa did not go with them to Miami. She stayed in Cuba to wait for her lover, as he told his granddaughter. The main character wondered if she was Che Guevara's daughter, as implied in Teresa's letters and diary. By using Roland Barthes' Semiotic theory and feminist approach, this paper investigates how a photograph can be given different meanings when it is given a different context or background story. Furthermore, how the image of the revolutionist Che Guevara changes from the image based on the fact we read from mainstream history books into the melancholic and romantic image of the same man in the novel when it was given a more personal approach toward the man in the photograph